2011
DOI: 10.1177/0194599811416318a65
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Management after Thyroidectomy: A Simple and Cost‐Effective Method

Abstract: Objective: Hypocalcemia is one of the principal complications of total or completion thyroidectomy. A number of different protocols for managing this potential complication have been published. Our simple postoperative regimen is described and the safety and cost-effectiveness assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…An all-inclusive prophylactic approach to preventing postoperative hypocalcemia is to routinely initiate treatment with oral calcium with or without calcitriol (41,42). This can be the most cost-effective approach because of the low cost of oral calcium preparations.…”
Section: Postoperative Prophylaxismentioning
confidence: 99%
“…An all-inclusive prophylactic approach to preventing postoperative hypocalcemia is to routinely initiate treatment with oral calcium with or without calcitriol (41,42). This can be the most cost-effective approach because of the low cost of oral calcium preparations.…”
Section: Postoperative Prophylaxismentioning
confidence: 99%
“…Routine calcium supplementation would save $29,365 per quality-adjusted life year (QALY), with a savings of $62 per patient and an incremental benefit of 0.002 QALYs [36]. Singer et al reported that the cost of a 3-week regimen of calcium carbonate is approximately $15, which is less expensive than either the cost of overnight admission or published laboratory protocols that are designed to predict the risk of hypocalcemia [37].…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 study from the US demonstrated that calcium supplementation is considerably less expensive than either the cost of overnight admission or adhering to published laboratory protocols designed to predict risk of hypocalcaemia, and that it is a safe and cost effective method of preventing hypocalcaemia. 19 Several large studies have demonstrated that thyroidectomy can be carried out both safely and effectively as a day procedure. Seybt and Terris had 208 same-day discharges (49.8%) and 210 patients (50.2%) admitted for a mean of 1.8 days.…”
Section: 18mentioning
confidence: 99%